Endoscopic Diagnosis and Treatment of a Case of Respiratory Papillomatosis. Issue 3 (1997) - Hirano, T.; Konaka, C.; Okada, S.; Shibanuma, H.; Shimizu, E.; Okunaka, T.; Sakai, H.; Ebihara, Y.; Kato, H.
Abstract : Respiratory papilloma is a rare lesion that arises in the larynx, trachea and bronchus. We describe a patient with laryngeal papilloma that spread to the trachea and which was effectively treated by Nd-YAG laser. Two years after the initial treatments of the laryngeal and tracheal papillomas, a recurrent lesion (solitary papilloma) was observed on the membranous portion of the trachea. We examined the recurrent lesion by bronchoscopy including bronchoscopic ultrasound (US), helical computed tomography (CT) and tracheal biopsies. Respiratory papillomatosis sometimes shows either malignant transformation or invasion to tracheal wall without displaying cytohistological atypia. Therefore, we concluded that bronchoscopic US and helical CT were useful for deciding on therapeutic strategy in cases of recurrence of tracheal papilloma.